IMPLEMENTATION OF COMMUNICATION ETHICS ACCORDING TO THE QUR'AN IN FAMILY EDUCATION: A CASE STUDY IN THE ASABRI PADANG COMPLEX - Hasnah, Radhiatul; Damanik, Iis Sholihat; Nurfadhilah, Nurfadhilah (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: This is motivated by ethical issues within the Indonesian Navy family environment due to communication patterns influenced by hierarchical culture, high discipline, and task pressure that impact the dynamics of husband, wife, and child relationships. Purpose: This study aims to determine communication ethics according to the Qur'an and its implementation in Indonesian Navy family education at the ASABRI Padang complex. Method: This study uses a descriptive qualitative approach to analyze communication ethics according to the Qur'an in Indonesian Navy family education. Data collection in this study uses observation and interview methods. The data analysis technique uses the Milles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Result: The results of the study include: first, communication ethics according to the Qur'an are understood from eight forms of qaul in the Qur'an, namely qaulan ma'rufa, qaulan sadida, qaulan baligha, qaulan karima, qaulan maisura, qaulan adzima, qaulan layyina, and qaulan tsaqila. Second, the application of communication ethics in Navy family education at the ASABRI Padang complex includes communication ethics for children towards their parents with appropriate, correct, noble, and gentle words, as well as communication ethics for parents towards their children with appropriate, easy-to-understand, and loving words. Conclusion: Based on the research that has been conducted, it can be concluded that communication ethics in accordance with the Qur'an are very necessary to be applied in the family environment in order to form Islamic character values. This is in line with the concept of Islamic education, which views communication as part of the process of tarbiyah and ta'dib (character building), so that the way a person communicates within the family and their environment will reflect their level of faith, morals, and intelligence spiritually, intellectually, and emotionally.